2014
DOI: 10.5483/bmbrep.2014.47.8.106
|View full text |Cite
|
Sign up to set email alerts
|

Global knockdown of microRNAs affects the expression of growth factors and cytokines in human adipose-derived mesenchymal stem cells

Abstract: Cell therapies utilizing mesenchymal stem cells (MSCs) have a great potential in many research and clinical settings. The mechanisms underlying the therapeutic effects of MSCs have been studied previously and the paracrine effects elicited by their production of various growth factors and cytokines were recognized as being crucial. However, the molecular controls that govern these paracrine effects remain poorly understood. To elucidate the molecular regulators of this process, we performed a global knockdown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Quantitative RT-PCR (qRT-PCR) showed a 60%–77% reduction in DGCR8 mRNA levels up to 10 days after siRNA transfection ( Supplementary Fig. S1A ) [ 27 ]. Immunoblot analysis confirmed the reduced DGCR8 protein levels in siDGCR8-transfected hMSCs ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative RT-PCR (qRT-PCR) showed a 60%–77% reduction in DGCR8 mRNA levels up to 10 days after siRNA transfection ( Supplementary Fig. S1A ) [ 27 ]. Immunoblot analysis confirmed the reduced DGCR8 protein levels in siDGCR8-transfected hMSCs ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…On day 1, the cells were transfected with 32 nM DGCR8 -targeting siRNAs (siDGCR8) or GFP control (siGFP; ST Pharm) using Lipofectamine 2000 (Invitrogen) according to the manufacturer's instructions. The siRNA sequences were previously described [ 27 , 28 ]: siGFP (sense, 5′-GUU CAG CGU GUC CGG CGA GT TdTdT-3'; antisense, 5′-CUC GCC GGA CAC GCU GAA CT TdTdT-3′) and siDGCR8 (sense, 5′-CAU CGG ACA AGA GUG UGA UdTdT-3'; antisense, 5′-AUC ACA CUC U UG UCC GAU GdTdT-3′). For transfection with miRNA mimics, 48 h after siDGCR8 transfection, 20 nM miR-20a-3p and miR-30c-5p mimics (Qiagen) were transfected using DharmaFECT1 (Thermo Fisher Scientific) following the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study we showed that knockdown of DGCR8, an indispensable component of miRNA biogenesis, results in abnormal cytokine secretion and the premature onset of cellular senescence in hMSCs [ 18 , 24 ]. Considering the impact of miRNAs in hMSCs, we hypothesized that additional dysregulated functions are linked to global miRNA knockdown.…”
Section: Resultsmentioning
confidence: 99%
“…This study was carried out according to the guidelines of the Institutional Review Board of Soon Chun Hyang University. hMSCs were isolated from human adipose tissue of three donors (age range of 42–51 years) and cultured as previously described ( 25 28 ). The hMSCs obtained were cultured in DMEM with 10% FBS, 100 units/ml penicillin and 100 μg/ml streptomycin (Gibco, Gaithersburg, MD, USA) in a humidified atmosphere containing 5% CO 2 at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…The RT 2 Profiler TM PCR Array Human Stem Cell (PAHS-405Z) (Qiagen, Hilden, Germany) was used as previously described ( 25 , 30 ). Briefly, 400 ng of total RNAs were treated with DNase I and then reverse transcribed using the RT 2 First Strand Kit (Qiagen, Hilden, Germany).…”
Section: Methodsmentioning
confidence: 99%